Left Ventricle Diastolic Wall Strain as a Simple Parameter of In-hospital Mortality in Heart Failure with Reduced Ejection Fraction (HFREF) Patients - Andrico Tobing (PRIMER (Prima Medical Journal), 2021)
Background: Abnormality of Left ventricle (LV) relaxation and LV stiffness are the major parts of LV diastolic dysfunction which have an important role in heart failure patients. Left ventricle Diastolic wall strain (DWS) is a non-invasive, load-independent, and reproducible estimator of LV stiffness using 2-D echocardiography based on linear elastic theory. Some studies have revealed the robust role of LV stiffness in heart failure with preserved ejection fraction (HFPEF) patients, but role and prognostic value of this parameter remains unclear in HFrEF. Methods: We studied 40 patients with signs and symptoms of heart failure (EF < 50%) between September to December 2017. Patients with the history of cardiac surgery, moderate to severe valvular heart disease, atrioventricular block, constrictive pericarditis, atrial fibrillation and old myocardial infarction in posterior wall are excluded. DWS was measured using the formula: DWS = [(LV posterior wall thickness at end systole − LV posterior wall thickness at end-diastole)/LV posterior wall thickness at end-systole]. All patients diverged into 2 groups (with and without in-hospital mortality) and DWS results were compared. Results: A total of 40 patients, 9 females (22%), with average age 59.6 ± 9.38 years. Hypertension in 18 patients (45%), type 2 Diabetes 22 patients (55%), Dyslipidemia 27 patients (67%). We found 14 patients (35%) with mortality in hospitalization. E/A ratio, E/E’ and DWS were significantly associated with in-hospital mortality. Between groups, DWS was significantly lower in patients with in-hospital mortality by 0.14  0.09 vs 0.22 ± 0.08 (P = 0.008). Although it is not statistically significant, lower DWS conversely related to diastolic dysfunction severity. Conclusion: DWS is associated with more severe outcome in HFrEF patients. As a simple and non-invasive parameter of LV stiffness, DWS can be useful to predict poor prognosis of HFrEF patients.